Peningkatan Kemampuan Berwirausaha Bagi Pelaku Usaha Ternak Puyuh Di Link Pesanggrahan Walantaka Kecamatan Walantaka Kota Serang - Nafiudin Nafiudin; Nana Umdiana (Universitas Serang Raya, 2019)
Limitations Knowledge about production and entrepreneurship ability generally makes it difficult for business actors to survive and develop, and this is what happens to business people in the guest house link in the Walanta village, Walantaka sub-district, Serang City. Based on these problems, we aim to provide solutions namely increasing entrepreneurship skills. for business people at Pesanggarahan Link, Walantaka District. By providing counseling and giving automatic egg incubators as an effort to increase the ability of entrepreneurship and foster an entrepreneurial spirit. The results of this service are an increase in entrepreneurial literacy and Increased Enthusiasm of Entrepreneurship for business actors and prospective new business actors Keeyword: Entrepreneurship Spirit, Entrepreneurial Ability